Review: Karakterisasi dan Modifikasi Membran Poliamida untuk Aplikasi Pemisahan Zat Warna - Yohana Ivana Kedang (Fakultas Pertanian, Universitas Timor, 2018)
Nanofiltration membranes occur due to the process of pressure differentials to separate the solut larger than the solution. This membrane is used in water purification processes, such as water softening, dye removal, and micropolutan removal. Membranes have several important criteria to determine membrane performance as filtration, namely flux (permeability), rejection (permectivity), thickness, morphology and mechanical properties of the membrane. This article is expected to provide ideas and recommendations regarding membrane characterization and the manufacture of nanofiltration membranes using modified polyamide membranes.